Artificial Intelligence, the Internet of Everything and the Scope and Scale of Seduction at the Boundaries of Law - Losavio, Michael M. (Public Governance, Administration and Finances Law Review, 2025)
Online and algorithmic systems can promote the emotional, intellectual and political seduction of people. The power and scope of these systems may create new threats against which traditional means of protection may be overwhelmed. We discuss possible legal and technical ways to combat such misconduct as to protect the innocent and the autonomy of the individual.